2015
DOI: 10.1155/2015/583106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nano-TiO2on the Toughness and Durability of Cement-Based Material

Abstract: The effects of nano-TiO2(NT) on microstructures and mechanical properties of cement mortars were studied by scanning electron microscopy (SEM), X-ray diffraction (XRD), and mercury intrusion porosimetry (MIP). Results show that 3% NT can remarkably increase the tensile/flexural strengths (i.e., the toughness is improved) and promote the precipitation of AFt crystal. The flexural and tensile strengths have significant positive correlation to the formation amount of AFt. The pores of mortars can be significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 30 publications
7
40
0
Order By: Relevance
“…This behavior was attributed to the addition of nTiO2 into the cementitious materials, which resulted in an accelerated rate of hydration process. A similar attribute has been reported in previous studies that when nTiO2 is uniformly distributed throughout the matrix, the hydration process and formation of C-S-H gel is accelerated, which results in early strength [32,[47][48]. In the other set of mixes, the effect of nTiO2 inclusion on the compressive strength of mixes was investigated after a different curing time.…”
Section: Compressive Strengthsupporting
confidence: 79%
See 3 more Smart Citations
“…This behavior was attributed to the addition of nTiO2 into the cementitious materials, which resulted in an accelerated rate of hydration process. A similar attribute has been reported in previous studies that when nTiO2 is uniformly distributed throughout the matrix, the hydration process and formation of C-S-H gel is accelerated, which results in early strength [32,[47][48]. In the other set of mixes, the effect of nTiO2 inclusion on the compressive strength of mixes was investigated after a different curing time.…”
Section: Compressive Strengthsupporting
confidence: 79%
“…S-H gel by increasing the amount of crystalline Ca(OH)2 at the early age of hydration [32,37]. Ma et al [32] reported 37% and 44% increase in tensile and flexural strength respectively for the samples containing TiO2. In addition, the results indicated that the addition of TiO2 could significantly refine the pores and shift them to the harmless pores.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, Italy, Belgium, China, and the United States, photocatalytic titanium dioxide (TiO 2 ) is added to sidewalk blocks, precast external building material, and the walls of large buildings such as theaters and stadiums; TiO 2 exhibits anti-fouling, deodorization, and air purification properties. Commercial TiO 2 is used in the construction of such conventional structures [4,5,6,7,8,9,10]. The most common crystalline phases of TiO 2 are rutile, anatase and brookite.…”
Section: Introductionmentioning
confidence: 99%